The relationship between ESL students' level of self-efficacy and their performance in reading and listening tests / Izlin Mohamad Ghazali - Mohamad Ghazali, Izlin (2013)
In second language learning, there has been continuous debate in identifying relationships of ESL students' attributes such as readiness, self-efficacy and language learning strategies to their language performance. This research aimed to investigate the relationship between the ESL students' reading and listening self-efficacy and their performance in reading and listening tests. Two instruments which were adapted in the instrumentation of study were "The ESL Learners' Self- Efficacy Scale in Reading Comprehension (English)" by Ghonsooly and Elahi (2011) and "A Questionnaire on EFL Learners' Self-Efficacy about Listening Skill" which was developed by Rahimi and Abedini (2009). The respondents of this study were the Diploma students of Universiti Teknologi MARA, Kelantan. A total of 300 sets of questionnaires were distributed and only 260 sets of questionnaires were returned. The Diploma students had also taken their BEL260 Midterm Test and Listening Test papers. The findings show that majority of the respondents have low reading and listening self-efficacy. This trait is also discovered to be directly related to their reading and listening scores. It is hoped that this research will become the starting point for other researchers to explore factors which lead to the ESL students' level of self-efficacy.